Epilepsy in the setting of full trisomy 18: A multicenter study on 18 affected children with and without structural brain abnormalities. Issue 3 (13th August 2016) - Matricardi, Sara; Spalice, Alberto; Salpietro, Vincenzo; Di Rosa, Gabriella; Balistreri, Maria Cristina; Grosso, Salvatore; Parisi, Pasquale; Elia, Maurizio; Striano, Pasquale; Accorsi, Patrizia; Cusmai, Raffaella; Specchio, Nicola; et al.
Abstract : This paper reports on the clinical aspects, electroencephalographic (EEG) features, and neuroimaging findings in children with full trisomy 18 and associated epilepsy, and compares the evolution and outcome of their neurological phenotype. We retrospectively studied 18 patients (10 males and 8 females; aged 14 months to 9 years) with full trisomy 18 and epilepsy. All patients underwent comprehensive assessment including neuroimaging studies of the brain. We divided patients into two groups according to neuroimaging findings: (Group 1) 10 patients harboring structural brain malformations, and (Group 2) 8 patients with normal brain images. Group 1 had a significantly earlier age at seizure onset (2 months) compared to Group 2 (21 months). The seizure semiology was more severe in Group 1, who presented multiple seizure types, need for polytherapy (80% of patients), multifocal EEG abnormalities and poorer outcome (drug resistant epilepsy in 90% of patients) than Group 2 who presented a single seizure type, generalized or focal, and non‐specific EEG pattern; these patients were successfully treated with monotherapy with good outcome. Imaging revealed a wide and complex spectrum of structural brain abnormalities including anomalies of the commissures, cerebellar malformations, cortical abnormalities, and various degrees of cortical atrophy. Epilepsy in full trisomy 18 may develop during the first months of life and can be associated with structural brain malformations. Patients with brain malformations can show multiple seizure types and can frequently be resistant to therapy with antiepileptic drugs. © 2016 Wiley Periodicals, Inc.